Cellular uptake of covalent and non-covalent DNA nanostructures with different sizes and geometries. Issue 22 (28th May 2019) - Raniolo, Sofia; Croce, Stefano; Thomsen, Rasmus P.; Okholm, Anders H.; Unida, Valeria; Iacovelli, Federico; Manetto, Antonio; Kjems, Jørgen; Desideri, Alessandro; Biocca, Silvia
Abstract : DNA nanostructures of different sizes and forms are internalized in cells through the LOX-1 receptor with different intracellular fate and lifetime. Abstract : DNA nanostructures with different sizes and shapes, assembled through either covalent or non-covalent bonds, namely tetrahedral and octahedral nanocages, rod-shaped chainmails, square box and rectangular DNA origami structures, were compared for their stability in serum, cell surface binding, internalization efficiency, and intracellular degradation rate. For cell internalization a specific cell system, highly expressing the scavenger receptor LOX-1 was used. The results indicate that LOX-1 binds and internalizes a broad family of DNA structures of different sizes that, however, have a different fate and lifetime inside the cells. Covalently linked tetrahedra, octahedra or chainmails are intact inside cells for up to 18 hours whilst the same DNA nanostructures without covalent bonds along with square box and rectangular origami are rapidly degraded. These data suggest that non-covalently linked structures may be useful for fast drug release whilst the covalently-linked structures could be appropriate vehicles for slow release of molecules.